“Goak Ngolol”, Tranformasi Jegog ke Jes Gamelan Fusion - I Putu Riangga Budi Pramana; I Gede Yudarta; Hendra Santosa (Journal of Music Science, Technology, and Industry, 2023)
Purpose: Music Composition "Goak Ngolol" is a form of composition created based on interest in the art of Jegog Jembrana. Methods: The research method used is a qualitative research method with a musicological perspective that focuses on aspects of the transformation of song motifs from Jegog to JES Gamelan Fusion through instrumentation techniques. Results and discussion: "Goak Ngolol" is an innovative character work created by I Nyoman Windha, S.Skar., M.A as a form of transformation of Jegog Jembrana characteristics to JES Gamelan Fusion characteristics. Jes Gamelan Fusion is a music community and a gamelan name coined by I Nyoman Windha. JES Gamelan Fusion is a form of creativity that combines two types of gamelan that is packed with innovative styles, but still rooted in Balinese characteristics. Two types of gamelan as the basic foundation are Jegog and Semar Pagulingan Saih Pitu. Implication: Although there is still Jegog in it, Jegog JES Gamelan Fusion is something different from Jegog in general, giving rise to the perspective of sound colors and game techniques as a new transformation of works.